Inflammation and neurological adverse drugs reactions: a case of long lasting impaired consciousness after oxatomide administration in a patient with gastroenteritis - Antoniazzi Stefania; Cattaneo Dario; Perrone Valentina; Carnovale Carla; Cherubini Simonetta; Mugolino Maria; Clementi Francesco; Zuccotti Gianvincenzo; Clementi Emilio; Radice Sonia (BMC, 2012)
Abstract Oxatomide at therapeutic doses generates occasionally drowsiness in children. When administered at toxic doses, however oxatomide may induce long lasting impaired consciousness. We now report a case of severe long lasting impaired consciousness induced by therapeutic doses of oxatomide occurring in a child affected by acute gastroenteritis. The clinical symptoms, the pharmacogenetic tests of polymorphisms in cytochrome P450 metabolizing enzymes (CYPs) and the clinical and laboratory analyses indicate that the enhanced drug sedative effect is likely due to an acute, yet mild, inflammatory state of the patient. These findings highlight the importance of assessing common, not serious inflammatory states when oxatomide is prescribed in paediatric patients.